Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1186/1471-2164-8-284
|View full text |Cite
|
Sign up to set email alerts
|

A detailed transcript-level probe annotation reveals alternative splicing based microarray platform differences

Abstract: Background: Microarrays are a popular tool used in experiments to measure gene expression levels. Improving the reproducibility of microarray results produced by different chips from various manufacturers is important to create comparable and combinable experimental results. Alternative splicing has been cited as a possible cause of differences in expression measurements across platforms, though no study to this point has been conducted to show its influence in cross-platform differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…Also, we have only used ~20,000 cross-annotated probes for performance analysis, which is less than 50% of the content. The reason for this strictness was, in part, based on a recent publication by Lee et al demonstrating high signal disagreement for probes targeting genes susceptible to alternative splicing [ 37 ]. We therefore limited our analysis to probes with identical targets.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we have only used ~20,000 cross-annotated probes for performance analysis, which is less than 50% of the content. The reason for this strictness was, in part, based on a recent publication by Lee et al demonstrating high signal disagreement for probes targeting genes susceptible to alternative splicing [ 37 ]. We therefore limited our analysis to probes with identical targets.…”
Section: Discussionmentioning
confidence: 99%
“…For most of the genes analyzed here, the expression patterns obtained from this analysis were found to be similar to that in microarray (Figure 4 ). The lack of correlation between the expression patterns in microarray and qRT-PCR in case of few genes in particular conditions, for example LOG in heat, LRK1 in drought etc., can be attributed to relatively lesser specificity of probes in microarray and array-platform bias (Lee et al 2007 ). Nevertheless, expression patterns obtained via qRT-PCR confirmed altered expression of these genes under various abiotic stress conditions.…”
Section: Resultsmentioning
confidence: 99%
“…However, failure of the oligonucleotide probes to detect all splice variants of the target gene may confound interpretation of the results. For example, a recent analysis of gene expression data obtained for different microarray platforms showed that genes exhibiting transcript variation had a lower signal agreement between platforms than did genes with less alternative splicing [ 20 ]. Array-Check enables the user to see at a glance which variants are targeted by a given microarray platform and, if desired, to compare the variants targeted by different microarray platforms (Figure 4 ).…”
Section: Utility and Discussionmentioning
confidence: 99%